### Reformatting the input :

Changes made to your input need to not impact the solution: (1): "x2" was changed by "x^2".

You are watching: How can this product be simplified 5x2(2x-3)

## Step 1 :

Equation in ~ the finish of step 1 :

(5x2 - 2x) - 3 = 0

## Step 2 :

Trying to element by separating the middle term2.1Factoring 5x2-2x-3 The an initial term is, 5x2 that coefficient is 5.The middle term is, -2x that coefficient is -2.The last term, "the constant", is -3Step-1 : main point the coefficient the the very first term through the consistent 5•-3=-15Step-2 : discover two components of -15 whose sum amounts to the coefficient that the center term, which is -2.

 -15 + 1 = -14 -5 + 3 = -2 That"s it

Step-3 : Rewrite the polynomial dividing the center term using the two factors found in step2above, -5 and also 35x2 - 5x+3x - 3Step-4 : add up the very first 2 terms, pulling out choose factors:5x•(x-1) include up the critical 2 terms, pulling out usual factors:3•(x-1) Step-5:Add increase the 4 terms the step4:(5x+3)•(x-1)Which is the wanted factorization

Equation at the finish of step 2 :

(x - 1) • (5x + 3) = 0

## Step 3 :

Theory - roots of a product :3.1 A product of number of terms equals zero.When a product of two or more terms equals zero, then at the very least one the the terms must be zero.We shall now solve every term = 0 separatelyIn various other words, we room going to solve as plenty of equations together there room terms in the productAny systems of hatchet = 0 solves product = 0 as well.

Solving a solitary Variable Equation:3.2Solve:x-1 = 0Add 1 come both political parties of the equation:x = 1

Solving a solitary Variable Equation:3.3Solve:5x+3 = 0Subtract 3 from both sides of the equation:5x = -3 division both political parties of the equation through 5:x = -3/5 = -0.600

Solving 5x2-2x-3 = 0 directly Earlier we factored this polynomial by separating the center term. Allow us now solve the equation by completing The Square and also by using the Quadratic Formula

Parabola, finding the Vertex:4.1Find the crest ofy = 5x2-2x-3Parabolas have a highest or a lowest allude called the Vertex.Our parabola opens up and as necessary has a lowest point (AKA absolute minimum).We understand this even prior to plotting "y" since the coefficient of the very first term,5, is positive (greater than zero).Each parabola has actually a vertical line of symmetry that passes v its vertex. Because of this symmetry, the heat of the contrary would, for example, pass through the midpoint of the two x-intercepts (roots or solutions) of the parabola. That is, if the parabola has indeed two actual solutions.Parabolas deserve to model countless real life situations, such together the height over ground, of things thrown upward, after ~ some duration of time. The vertex of the parabola can provide us through information, such as the maximum height that object, thrown upwards, can reach. Therefore we want to have the ability to find the coordinates of the vertex.For any kind of parabola,Ax2+Bx+C,the x-coordinate the the crest is given by -B/(2A). In our situation the x name: coordinates is 0.2000Plugging right into the parabola formula 0.2000 for x we can calculate the y-coordinate:y = 5.0 * 0.20 * 0.20 - 2.0 * 0.20 - 3.0 or y = -3.200

Parabola, Graphing Vertex and also X-Intercepts :

Root plot for : y = 5x2-2x-3 Axis of the opposite (dashed) x= 0.20 Vertex in ~ x,y = 0.20,-3.20 x-Intercepts (Roots) : root 1 in ~ x,y = -0.60, 0.00 root 2 at x,y = 1.00, 0.00

Solve Quadratic Equation by perfect The Square

4.2Solving5x2-2x-3 = 0 by perfect The Square.Divide both sides of the equation by 5 to have 1 as the coefficient the the very first term :x2-(2/5)x-(3/5) = 0Add 3/5 to both next of the equation : x2-(2/5)x = 3/5Now the clever bit: take the coefficient the x, which is 2/5, divide by two, providing 1/5, and finally square it giving 1/25Add 1/25 come both political parties of the equation :On the right hand side us have:3/5+1/25The common denominator of the two fractions is 25Adding (15/25)+(1/25) offers 16/25So adding to both political parties we ultimately get:x2-(2/5)x+(1/25) = 16/25Adding 1/25 has actually completed the left hand side into a perfect square :x2-(2/5)x+(1/25)=(x-(1/5))•(x-(1/5))=(x-(1/5))2 points which space equal to the exact same thing are also equal come one another. Sincex2-(2/5)x+(1/25) = 16/25 andx2-(2/5)x+(1/25) = (x-(1/5))2 then, follow to the regulation of transitivity,(x-(1/5))2 = 16/25We"ll refer to this Equation as Eq.

See more: Can You Ingest Vicks Vapor Rub On Your Feet Help With A Cough?

#4.2.1 The Square root Principle states that when two things are equal, your square roots space equal.Note that the square source of(x-(1/5))2 is(x-(1/5))2/2=(x-(1/5))1=x-(1/5)Now, using the Square source Principle to Eq.#4.2.1 us get:x-(1/5)= √ 16/25 add 1/5 to both sides to obtain:x = 1/5 + √ 16/25 since a square root has two values, one positive and the other negativex2 - (2/5)x - (3/5) = 0has 2 solutions:x = 1/5 + √ 16/25 orx = 1/5 - √ 16/25 note that √ 16/25 deserve to be written as√16 / √25which is 4 / 5